Efficient and Consistent Orthotopic Osteosarcoma Model by Cell Sheet Transplantation in the Nude Mice for Drug Testing - Wu, Hongwei; He, Zhengxi; Li, Xianan; Xu, Xuezheng; Zhong, Wu; Bu, Jie; Huang, Gang (Frontiers in Bioengineering and Biotechnology, 2021)
Osteosarcoma (OS) is a big challenge on clinical treatment. The breakthrough associated with osteosarcoma in basic research and translational research depend on the reliable establishment of animal model，whereby mice are frequently used. However, a traditional animal modeling technique like tumor cell suspension injection, causes batch dynamics and large mice consumption. Here we suggested a novel approach in establishing an orthotropic osteosarcoma model in nude mice rapidly through cell sheet culture and transplantation. Our findings demonstrated that the 143b osteosarcoma cell sheet orthotopically implanted into the nude mice could form a visible mass within 10 days, whereas it took > 15 days for similar amount of cell suspension injection to form visible tumor mass. Living animal imaging results showed that tumor formation rate was 100% in the cell sheet implantation group, while it was 67% in the cell suspension injection group. The formed tumor masses were highly consistent in both growth rate and tumor size. Massive bone destruction and soft tissue mass formation were observed from Micro CT analysis, suggesting presence of osteosarcoma. Histopathological analysis demonstrated that the orthotropic osteosarcoma model mimicked the tumor bone growth, bone destruction as well as the lung metastasis. These findings imply that such a cell sheet technology could be an appropriate approach to rapidly establish a sustainable orthotropic osteosarcoma model for tumor research and reduce mice consumption.